2019
DOI: 10.3390/socsci8020033
|View full text |Cite
|
Sign up to set email alerts
|

Commodifying Lisbon: A Study on the Spatial Concentration of Short-Term Rentals

Abstract: This article explores the relationship between the spatial concentration of short-term rentals in Lisbon’s historic center and the phenomena of uneven development and tourism gentrification. By providing quantitative and qualitative evidence of the uneven geographic distribution of tourist apartments within the municipality of Lisbon, it contributes to the study of the new processes of neoliberal urbanization in the crisis-ridden countries of Southern Europe. It argues that the great share of whole-home rental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
2

Year Published

2020
2020
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 31 publications
0
10
0
2
Order By: Relevance
“…The improvements to the transportation network and increase in purchasing power during the 1970s and 1990s allowed many families to move to the surrounding municipalities, relegating the city centre to older citizens (24%) and immigrants (11%) [ 42 ]. Recently, tourism has changed this pattern, with many buildings being renovated and adapted for local touristic accommodation, resulting in displacement and gentrification in several historic neighborhoods [ 43 , 44 ].…”
Section: Methodsmentioning
confidence: 99%
“…The improvements to the transportation network and increase in purchasing power during the 1970s and 1990s allowed many families to move to the surrounding municipalities, relegating the city centre to older citizens (24%) and immigrants (11%) [ 42 ]. Recently, tourism has changed this pattern, with many buildings being renovated and adapted for local touristic accommodation, resulting in displacement and gentrification in several historic neighborhoods [ 43 , 44 ].…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, they found that Airbnb tourism listings were growing in areas with a higher proportion of privately-rented properties, turning an increasing percentage of the original housing supply into short-term rental supply. For Lestegás et al (2019), this rent gap, originated by the latest wave of tourism growth, takes place especially in big cities but is really a global issue: the loss of purchasing power in many countries after the financial crisis hit, and the subsequent austerity measures, forced many residents to compete for access to a limited housing stock controlled by real-estate developers targeting external markets, essentially international tourists and other temporary (mostly high-income and professionally-qualified) visitors (sometime described as "digital nomads"). Meanwhile, different authors have found that this rent gap is also rooted in the increasing commercial orientation of a large proportion of Airbnb's hosts.…”
Section: Literaturementioning
confidence: 99%
“…Indeed, the increasing relevance of tourism has had major impacts on the real estate market, the situation has led to an imbalance of the access to long-term rental, while competing in a market that favours short-term rental. The regulation of such a balance has become one of the greatest challenges for urban management (Lestegás, Seixas, & Lois-González, 2019;Malet Calvo et al, 2018).…”
Section: Case Study Alfama and Lisbon As A Trending Tourism Destinationmentioning
confidence: 99%